2019
DOI: 10.3390/molecules24224029
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Curcumin on the Differentiation of Mesenchymal Stem Cells into Mesodermal Lineage

Abstract: Curcumin has been placed at the forefront of the researcher’s attention due to its pleiotropic pharmacological effects and health benefits. A considerable volume of articles has pointed out curcumin’s effects on the fate of stem cell differentiation. In this review, a descriptive mechanism of how curcumin affects the outcome of the differentiation of mesenchymal stem cells (MSCs) into the mesodermal lineage—i.e., adipocyte, osteocyte, and chondrocyte differentiation—is compiled from the literature. The section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 88 publications
0
21
0
Order By: Relevance
“…Curcumin, a natural phenolic biphenyl compound derived from the plant Curcuma longa, is an antioxidant with anti-inflammatory and osteogenesis-regulating effects [ 83 , 84 ]. In BMSCs, curcumin facilitates differentiation towards osteoblasts by activating Akt/GSK3 β and Wnt/ β -catenin pathways [ 85 ]. Docosahexaenoic acid (DHA) belongs to the omega-3 polyunsaturated fatty acids, and it is well-known for being protective against inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin, a natural phenolic biphenyl compound derived from the plant Curcuma longa, is an antioxidant with anti-inflammatory and osteogenesis-regulating effects [ 83 , 84 ]. In BMSCs, curcumin facilitates differentiation towards osteoblasts by activating Akt/GSK3 β and Wnt/ β -catenin pathways [ 85 ]. Docosahexaenoic acid (DHA) belongs to the omega-3 polyunsaturated fatty acids, and it is well-known for being protective against inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the fact that Cur possesses pleiotropic activity could be attributed to their activation and protection effects on MSCs [ 31 , 32 ]. Several studies have confirmed that Cur is involved in regulating the immunomodulatory capabilities; the differential potential of MSCs to different cell lineages (neurocyte, chondrocyte, adipocyte, and osteoblast), and in multiple signaling mechanisms is involved in this process [ 28 , 31 , 33 , 34 , 35 ]. Moreover, Cur is also regarded as a good antioxidant by which to improve the lifespan of rat adipose tissue-derived mesenchymal stem cells (ADSCs) due to the increase in the telomerase reverse transcriptase (TERT) gene expression [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the earlier reports, curcumin, a natural polyphenol compound, reduces osteoclastic formation and maturation by acting on the RANKL site [56]. It was also shown to inhibit c-fos and c-jun (AP-1) expression, responsible for the differentiation into osteoclasts [57].…”
Section: Discussionmentioning
confidence: 99%